Comprehensive Antibody Epitope Mapping of the Nucleocapsid Protein of Severe Acute Respiratory Syndrome (SARS) Coronavirus: Insight into the Humoral Immunity of SARS - Liang, Yunfei (Clin Chem, 2005)
Background: The epidemic outbreak of severe acute respiratory syndrome (SARS) posed a worldwide threat to public health and economic stability. Although the pandemic has been contained, concerns over its recurrence remain. It is essential to identify specific diagnostic agents and antiviral vaccine candidates to fight this highly contagious disease. Methods: We generated 14 monoclonal antibodies (mAbs) specific to the SARS coronavirus (SARS-CoV) nucleocapsid (N) protein and used these to thoroughly map the N protein antigenic determinants. We identified the immunodominant antigenic sites responsible for the antibodies in sera from SARS patients and antisera from small animals and differentiated the linear from the conformational antibody-combining sites comprising the natural epitopes by use of yeast surface display. Results: We identified 5 conformational and 3 linear epitopes within the entire N protein; 3 conformational and 3 linear epitopes were immunodominant. The antibody responses to the N protein fragments in mammalian sera revealed that 3 regions of the N protein are strong antigenic domains. We expanded the specificity of the N protein epitope and identified 4 novel conformational epitopes (amino acids 1–69, 68–213, 212–341, and 337–422). Conclusion: The antigenic structures identified for the SARS-CoV N protein, the epitope-specific mAbs, and the serum antibody profile in SARS patients have potential use in the clinical diagnosis and understanding of the protective immunity to SARS-CoV.